THE MODERN HISTORY OF UZBEKISTAN - Makhkamova Nadira Ulfatdjanovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores perspectives and conclusions regarding recent historical events in Uzbekistan. Located in the heart of Central Asia, Uzbekistan boasts a rich cultural heritage and ancient history spanning thousands of years. In recent decades, the country has undergone significant changes characterized by economic growth, political reforms, and diverse socio-cultural transformations. One key aspect of Uzbekistan’s recent history is the emphasis on economic development.